2011
DOI: 10.1021/la202123e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Lipid–Polymer Hybrid Nanoparticles with pH-Triggered Poly(ethylene glycol) Shedding

Abstract: Novel lipid-polymer hybrid nanoparticles are designed with a poly(ethylene glycol) coating that is shed in response to a low pH trigger. This allows the nanoparticles to be stable during systemic circulation and at neutral pH, but destabilize and fuse with lipid membranes in acidic environments. The hybrid nanoparticles consist of a poly(lactic-co-glycolic acid) core with a lipid and lipid-PEG monolayer shell. To make the hybrid nanoparticles pH sensitive, a lipid-(succinate)-mPEG conjugate is synthesized to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 29 publications
1
53
0
Order By: Relevance
“…Collectively, all of these features make the lipid-based surface engineering strategies ideal for improving the clinical performance of PNPs [18, 24]. Although enormous progress has been made in the area of nanoengineering, many challenges remain that potentially hinder the translation of PNPs to the clinical arena [5, 54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, all of these features make the lipid-based surface engineering strategies ideal for improving the clinical performance of PNPs [18, 24]. Although enormous progress has been made in the area of nanoengineering, many challenges remain that potentially hinder the translation of PNPs to the clinical arena [5, 54].…”
Section: Resultsmentioning
confidence: 99%
“…Differentially charged synthetic phospholipids, such as zwitterionic, cationic, anionic, and neutral phospholipids (e.g., DOTAP, and sterol lipids such as cholesterol), are often used in biomedical engineering [13, 15]. Polyethylene glycol (PEG) is a hydrophilic lipid that has been largely applied to improve the circulation half-life of NPs in blood [17, 18, 23, 24]. The amphiphilic nature of phospholipids allows them to form organized structures, such as vesicles or membranes, when immersed in an aqueous environment.…”
Section: Lipid-based Surface Engineering Of Plga Nanoparticlesmentioning
confidence: 99%
“…22 To solve these issues, PEG shedding in response to intracellular environments has been proposed. [23][24][25] More recently, a novel biocompatible and biodegradable PEG-polypeptide catiomers bearing a PEG-sheddable shell and a disulfide-linked PEG-poly(ε-benzyloxycarbonyl-l-lysine) block copolymer (PEG-SS-PLL) was developed in our laboratory. It was found that the PEG-SS-PLL catiomer effectively delivered plasmid DNA into HeLa cells in vitro with negligible cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Another surface modification relates to the acidic environment of tumors. A pH-sensitive PEG coating shed its coating under the acidic condition, fused with cell membrane and entered into tumor cells (92). A red blood cell approach to particle surface functionalization was made by coating biodegradable PNPs with natural erythrocyte membranes.…”
Section: Surface Modifications Of Cslphnpsmentioning
confidence: 99%
“…Various classes of LPHNPs are summarized in Table 1-1 and are classified depending on the arrangement of lipid and polymer in the hybrid system. Due to their perceived advantages over other existing hybrid systems, significant effort has been directed towards the understanding of CSLPHNPs (92)(93)(94)(95)(96)(97)(98)(99)(100)(101). The primary objective of this review article is to discuss CSLPHNPs which are composed of polymeric core and lipid shell.…”
Section: Review Of Hybrid Nanoparticles Literature Introductionmentioning
confidence: 99%